Effect of Stenochlaena palustris and Mikania micrantha Extracts as Insecticides against Sitophilus Spp. on Maize Seeds - Fitriani Fitriani; Lipacoy Turnip; Kartika aprilia putri; Beni Al Fajar; Yonadiah Dwitya (Journal of Global Sustainable Agriculture, 2026)
Infestation by Sitophilus spp. in maize seeds during storage can reduce seed quality and viability. The use of botanical insecticides derived from local plants offers a potential eco-friendly control alternative. This study aimed to evaluate the effectiveness of a mixture of Stenochlaena palustris and Mikania micrantha powders as a botanical insecticide against Sitophilus spp. and to assess its impact on maize seed viability. An experimental approach using a Completely Randomized Design (CRD) was employed, comprising six treatments and five replicates: a positive control, a negative control, and mixtures of the two plant powders (1:1 ratio) at dosages of 1 g, 2 g, 3 g, and 4 g per 30 maize seeds. Each experimental unit was infested with three pairs of adult Sitophilus spp. Parameters observed included insect mortality, infestation intensity, seed weight loss, and germination capacity after 30 days of storage. Data were analyzed using Analysis of Variance (ANOVA) at a 5% significance level, followed by Duncan’s Multiple Range Test (DMRT). The results indicated that the treatments significantly affected insect mortality and seed viability. The mixture of S. palustris and M. micrantha  powders at the highest dosage demonstrated the greatest effectiveness, achieving 100% mortality, an infestation intensity of ≤0.27%, and seed weight loss of ≤4.5%. Furthermore, seed viability remained high, with germination reaching 100% by day 7. Thus, the mixture of S. palustris  and M. micrantha powders shows potential as an effective botanical insecticide for controlling Sitophilus spp. in stored maize seeds